Enhancing Pupils’ Speaking Skill through Using English Songs - Goufa, Imene (My University, 2020)
Acquiring new vocabulary items so as to speak is a challenge. Teachers may provide their learners with an acceptable amount of vocabularies but the problem is that they do not show their learners how to acquire and how to memorize it for any future speaking. This study was designed for the purpose of investigating the role of English songs in enhancing speaking skill. The aim of this research is to discover whether English songs can be a motivational tool in helping pupils to speak during oral expression. Three different tools were used in order to collect data. A questionnaire was given to thirty-one pupils of third year middle school, an observation and an experiment was made in order to refute or confirm the hypothesis. The findings indicate that the use of English songs in the classroom is motivating in helping pupils to speak during oral expression.
Case of study: Third Year Middle School at IKHWA SOUSSI – Relizane.
Keywords: Speaking Skill; English Songs; Vocabulary Acquisition